What will radiation oncology look like in 2050?: a look at a changing professional landscape in Europe and beyond - Baumann, Michael; Ebert, Nadja; Kurth, Ina; Bacchus-Wermke, Carol; Overgaard, Jens (Molecular oncology, 2020)
The number of newly diagnosed cancers per year is predicted to almost double in the next two decades worldwide, and it remains unclear if and when this alarming trend will level off or even reverse. As such, cancer is very likely to continue to pose a major threat to human health. Radiation oncology is an indispensable pillar of cancer treatment and a well-developed discipline. Nevertheless, key trends in cancer research and care, including improved primary prevention, early detection, integrated multidisciplinary approaches, personalized strategies at all levels of care, value-based assessments of healthcare systems, and global health perspectives, will all shape the future of radiation oncology. Broader scientific advances, such as rapid progress in digitization, automation, and in our biological understanding of cancer, as well as the wider societal view of healthcare systems will also influence radiation oncology and how it is practiced. To stimulate a proactive discussion on how to adapt and reshape our discipline, this review provides some predictions on what the role and practice of radiation oncology might look like in 30 years’ time.